Developing efficient circularity for construction and demolition waste management in fast emerging economies: Lessons learned from Shenzhen, China - Bao, Zhikang; Lu, Weisheng (The Science of the total environment, 2020)
Proper management of construction and demolition (C&D) waste is a key challenge amid global advocacy of the circular economy. This is of particular urgency in fast-emerging economies, where economic development induces massive construction without the capacity to manage the associated waste. This paper reports lessons learned from Shenzhen, China, which has witnessed exciting economic growth in the past few decades but also been compelled to rapidly develop an effective C&D waste circular economy from a low base. The research adopts a mixed-method approach combining case study, site investigations, and interviews in Shenzhen. It is discovered that Shenzhen's success can be attributed to (a) implementing strong governmental interventions; (b) developing a thriving C&D waste recycling market; (c) introducing advanced recycling technologies; and (d) enacting responsive institutional arrangements. Further improvements related to (1) recycled product certification, (2) land use and economic subsidies, and (3) changing circular economy philosophies, inter alia, are desired to sustain the long-term prosperity of this circular economy. The research provides a reference which can be adapted to the unique context of other emerging economies in developing effective circularity. [Display omitted] •Some lessons learnt from Shenzhen's C&D waste recycling industry are summarized.•The lessons are useful for emerging economies to develop efficient circularity.•Some further improvements to sustain the long-term prosperity are also reported.